Cesarean delivery and its determining factors: A hospital-based study in Jashore District, BangladeshWhat This Study Adds:Policy Implications: - Md. Sakhawot Hossain; Suvasish Das Shuvo; Sharmin Asha; Md. Raihan Chodhoury; Md. Toufiq Elahi (Elsevier, 2024)
Background: The rising prevalence of cesarean deliveries (CD) is a major public health problem worldwide, especially in Bangladesh. This study aims to investigate the prevalence and factors associated with cesarean deliveries in the Jashore district of Bangladesh. Study design: This cross-sectional study, conducted from December 2022 to February 2023 in Jashore district, Bangladesh, involved face-to-face interviews with 662 mothers during hospital visits. Methods: A pretested, structured, and validated questionnaire was employed to gather information on socioeconomic characteristics, obstetric history, maternal healthcare utilization, and factors influencing the choice of delivery method. Multinomial logistic regression models were employed to assess and predict determining factors influencing cesarean delivery. Results: The study revealed a high cesarean delivery (CD) prevalence of 70.5 %, exceeding the WHO-recommended threshold. Key socioeconomic factors associated with increased CD rates included rural residence, younger maternal age (15-20 years), nuclear family structure, and husbands in business. Additionally, private hospital deliveries, a history of previous CD, maternal self-preference, and doctor's influence were significant predictors of CD. The majority of participants believed CD enhances maternal safety (74.6 %) and alleviates pain (74.8 %). Conclusion: The high rate of cesarean deliveries in Jashore highlights the need for public health interventions that improve access to quality maternal care and promote evidence-based decision-making. Reducing unnecessary cesarean procedures, particularly in private hospitals, and enhancing patient education can significantly improve maternal and neonatal health outcomes.